Tension pneumocephalus as a complication of surgical evacuation of chronic subdural hematoma: case report and literature review - Mohammed A. Azab; Ahmed Hazem; Brandon Lucke-Wold (Exploration of Neuroprotective Therapy, 2023)
The management of symptomatic chronic subdural hematoma (CSDH) is surgical evacuation and prognosis in most cases is good. Tension pneumocephalus is the presence of air under pressure in the intracranial cavity. A case of tension pneumocephalus developing as a complication of burr hole evacuation of CSDH is illustrated. In this case, tension pneumocephalus was managed by reopening the wound and saline irrigation with a subdural drain placement. Considering this case report and after a careful review of the literature, the physiopathology, diagnosis, and treatment of this complication are highlighted in the article.